Intrinsic Ferromagnetism in Mn‐Substituted MoS2 Nanosheets Achieved by Supercritical Hydrothermal Reaction. Issue 39 (21st August 2017) - Tan, Hao; Hu, Wei; Wang, Chao; Ma, Chao; Duan, Hengli; Yan, Wensheng; Cai, Liang; Guo, Peng; Sun, Zhihu; Liu, Qinghua; Zheng, Xusheng; Hu, Fengchun; et al.
Abstract: Doping atomically thick nanosheets is a great challenge due to the self‐purification effect that drives the precipitation of dopants. Here, a breakthrough is made to dope Mn atoms substitutionally into MoS2 nanosheets in a sulfur‐rich supercritical hydrothermal reaction environment, where the formation energy of Mn substituting for Mo sites in MoS2 is significantly reduced to overcome the self‐purification effect. The substitutional Mn doping is convincingly evidenced by high‐angle annular dark‐field scanning transmission electron microscopy and X‐ray absorption fine spectroscopy characterizations. The Mn‐doped MoS2 nanosheets show robust intrinsic ferromagnetic response with a saturation magnetic moment of 0.05 µ B Mn −1 at room temperature. The intrinsic ferromagnetism is further confirmed by the reversibility of the magnetic behavior during the cycle of incorporating/removing Li codopants, showing the critical role of Mn 3d electronic states in mediating the magnetic interactions in MoS2 nanosheets. Abstract : A supercritical hydrothermal reaction method is used to substitutionally dope Mn atoms into MoS2 nanosheets, as convincingly evidenced by high‐angle annular dark‐field and X‐ray absorption fine spectroscopy characterizations. The as‐prepared nanosheets show robust intrinsic ferromagnetic response with a saturation magnetic moment of 0.05 µ B Mn −1 at room temperature, which can be tuned by reversible incorporation/removal of Li codopants.